Exploring Syariah-Based Tourism at The Tomb Syekh Wasil Kediri in The Framework of SDGs and Maqashid Al-Shariah - Zunaidi, Arif; Maghfiroh, Fachrial Lailatul; Ubaidah, Arjuna Nur Chasan Al; Dafabiano, Lintang Ageng (Proceedings of Annual Conference for Muslim Scholars, 2025)
Religious tourism plays an important role in connecting cultural heritage with sustainable economic growth. This study analyzes the tomb Syekh Wasil Kediri as a center of syariah-based tourism where faith, heritage, and community development converge. Using a qualitative approach through field observations, stakeholder interviews, and document analysis, the research explores how this destination supports local economic empowerment while aligning with maqashid al-shariah and the Sustainable Development Goals (SDGs). The findings show that syariah-based tourism generates income for surrounding communities and preserves cultural–spiritual heritage. Activities at the site embody the objectives of maqashid al-shariah by protecting religion, life, intellect, lineage, and wealth, consistent with SDGs on decent work, sustainable cities, and cultural sustainability. Integrating religious values with heritage management offers a holistic model of sustainable tourism and contributes to broader discussions on Islamic economics and heritage-based development applicable to other religious destinations.